2014
DOI: 10.1371/journal.pone.0098177
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Depth of Interaction upon the Performance of Scintillator Detectors

Abstract: The uncertainty in time of particle detection within a scintillator detector, characterised by the coinci- dence time resolution (CTR), is explored with respect to the interaction position within the scintillator crystal itself. Electronic collimation between two scintillator detectors is utilised to determine the CTR with depth of interaction (DOI) for different materials, geometries and wrappings. Significantly, no rela- tionship between the CTR and DOI is observed within experimental error. Confinement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Even though the DOI time offset issue has been studied in the past through Monte Carlo simulations (Brunner et al 2013) and experimental measurements (Brown et al 2014), the limitation of an analytical approach such as the MergedPTS model to study this time offset impact on CTR was not highlighted previously in the literature. This is likely due to the relatively limited influence of the PTS on CTR when compared to the combination of emission rate and SPTR for the typical detectors available today.…”
Section: Mergedpts Model For Typical Detectorsmentioning
confidence: 99%
“…Even though the DOI time offset issue has been studied in the past through Monte Carlo simulations (Brunner et al 2013) and experimental measurements (Brown et al 2014), the limitation of an analytical approach such as the MergedPTS model to study this time offset impact on CTR was not highlighted previously in the literature. This is likely due to the relatively limited influence of the PTS on CTR when compared to the combination of emission rate and SPTR for the typical detectors available today.…”
Section: Mergedpts Model For Typical Detectorsmentioning
confidence: 99%
“…A possible way to compensate the effect of the PTS would be double-sided readout of the crystal with correction for depth of interaction (DOI). However, CTR measurements of Brown et al (2014) showed that from standard scintillation no improvements were observed if the scintillation is confined to a fixed DOI. Nevertheless, double-sided readout of 20 mm long crystals would still have the advantage of reducing parallax-errors in PET because of the DOI information, and would furthermore allow better CTRs due to higher light collection comparable to that of 10 mm long, single-sided readout, crystals (Gundacker 2014).…”
Section: Discussionmentioning
confidence: 96%
“…An accurate measure of scale is of interest as this can be used to find depth of interaction within the scintillator and therefore to improve energy resolution [55]. Also of interest is the predicted total blob intensity -the sum of all blob pixels excluding background -which indicates accurate reconstruction of deposited energy.…”
Section: Prediction Of Scale and Energymentioning
confidence: 99%